Microencapsulated Neural Stem Cells Inhibit Sciatic Nerve Injury-Induced Pain by Reducing P2 × 4 Receptor Expression - Zhang, Wen-jun; Luo, Chen; Huang, Chao; Liu, Si-cheng; Luo, Hong-liang (Frontiers in Cell and Developmental Biology, 2021)
Objectives: The purpose of this study is to investigate the effects of transplantation of microencapsulated neural stem cells (MC-NSCs) down-regulates the P2X4 receptors (P2X4Rs) over-expression and relieve neuropathic pain (NPP). Methods: Neural stem cells (NSCs) and MC-NSCs were transplanted to the injured sciatic nerve. Transmission electron microscope and immunofluorescence were performed to observe the changes of injured sciatic nerve. Behavioral methods were performed to detect mechanical withdrawal thresholds (MWT) and thermal withdrawal latency (TWL) of rats. Expression levels of P2X4Rs and p-p65 in the spinal cord segment of rats were measured by using molecular biology methods. The concentrations of IL-1β and TNF-α were detected in serum of rats by ELISA. Results: After sciatic nerve injury, the sciatic nerve fibers had the myelinated lamina separated, and disintegrated fragments could be seen. The fluorescence intensity of myelin MBP was weaken. The MWT and TWL were significantly decreased, the expression of P2X4Rs and p-p65 were significantly increased, and the concentrations of IL-1β and TNF-α were increased. After NSCs and MC-NSCs transplantation, the myelin sheath of the sciatic nerve was relatively intact, some demyelination changes could be seen, and the injured sciatic nerve has been improved. The fluorescence intensity of myelin MBP was increased. The MWT and TWL were increased, expression levels of P2X4Rs and p-p65 were decreased, and the concentrations of IL-1β and TNF-α were significantly decreased. Compared with NSCs transplantation, transplantation of MC-NSCs could better repair the damaged sciatic nerve, decrease the expression of P2X4Rs and p-p65, decrease the level of IL-1β and TNF-α, and relieve pain (all P value < 0.05). Conclusions: NSCs and MC-NSCs transplantation may alleviate pain by reducing the expression of P2X4Rs and inhibiting the activation of NF-KB signaling. While MC-NSCs transplantation has a better effect of suppressing pain. Our experimental results provide new data support for the treatment of NPP.